2021
DOI: 10.1063/5.0053847
|View full text |Cite
|
Sign up to set email alerts
|

Synopsis of Vogel–Escudier flow

Abstract: The topology and the dynamics of Vogel–Escudier flow, which is the flow inside a circular cylinder with a top rotating lid, are presented in this paper. A three-dimensional direct numerical simulation of the Navier–Stokes equations in cylindrical coordinates is used to investigate the flow. Various combinations of Reynolds number and aspect ratio are studied and classified based on the flow topology. The flow is found to exhibit steady axisymmetric, unsteady axisymmetric, rotating azimuthal waves, and weak tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…The present work focuses on the non-axisymmetry in and around the breakdown region and we show that the chaotic state of the flow coincides with the appearance of the TG-like vortices, which has been overlooked in the previous studies. The presence of TG-like vortices in the side-wall boundary layer has also been reported briefly in earlier works [10,24,25] at high Reynolds numbers. We examine the bifurcation of the VE flow to a chaotic state that exhibits the TG-like vortices in the side-wall boundary layer.…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…The present work focuses on the non-axisymmetry in and around the breakdown region and we show that the chaotic state of the flow coincides with the appearance of the TG-like vortices, which has been overlooked in the previous studies. The presence of TG-like vortices in the side-wall boundary layer has also been reported briefly in earlier works [10,24,25] at high Reynolds numbers. We examine the bifurcation of the VE flow to a chaotic state that exhibits the TG-like vortices in the side-wall boundary layer.…”
Section: Introductionsupporting
confidence: 73%
“…The unsteadiness of the flow can be observed from the velocity signal shown in figure 2 e , which shows multiple frequencies in the flow. Sharma & Sameen [24] have shown that the wavenumber of the azimuthal mode in the flow depends on the aspect ratio of the cylinder. The reconstructed phase space in figure 2 f indicates that the flow is in a quasi-steady state.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations